Impact of the I-PASS Communication Method on Nurse Handover Quality in Hospital Settings: A Scoping Review - Agnes Stephania Penu; Ati Surya Mediawati; Hana Rizmadewi Agustina (Journal of Health and Nutrition Research, 2026)
Effective handover communication is a crucial element in ensuring patient safety and continuity of care in clinical settings. Communication errors during handovers frequently lead to medical errors and adverse events. The I-PASS method was developed as a structured solution to address these challenges. This study aims to identify and synthesize evidence regarding the impact of implementing the I-PASS communication method on the quality of nurse handovers and its contribution to improving patient safety. A comprehensive literature search was conducted across four major databases (Science Direct, EBSCO, PubMed, and Scopus) from December 2024 to September 2025, using keywords such as "Nurse”, "I-PASS Method," "Communication”, “Quality Handover” and "Patient Safety". Nine articles met the inclusion criteria, comprising quantitative, prospective, observational, and quasi-experimental studies published in English between 2015-2025. A total of 9 studies were included in this review. This study found five themes of impact I-PASS communication methods on the quality of nurse handovers. The implementation of I-PASS was associated with reduction in communication errors, improvement information quality, medical staff satisfaction, time efficiency, as well as patient and family engagement. While the effectiveness of I-PASS has been demonstrated across various contexts, implementation challenges such as environmental interruptions and the need for managerial support remain.